The Development and Assessment of Crayons that Produce Textured Lines for Individuals Who Are Visually Impaired. (March 2019) - Kandalam, Suraj; Ferro, Tyler; Pawluk, Dianne T. V.
Introduction: This article describes the development and initial assessment of a set of tactile crayons that can produce different textured lines and areas on standard paper. Method: An assessment of the need for tactile crayons was performed through the use of surveys and focus groups from which a set of six tactile crayons was developed. Development was focused on being able to differentiate the crayons along the texture dimensions of sticky or slippery, rough or smooth, and hard or soft in informal dimensional analysis. Preliminary discrimination testing was performed to determine the viability of the six selected crayons. The main assessment determined whether individuals were able to identify each of the crayons by number from feeling scribbles on paper. Results: User needs assessment showed that many practitioners felt the development of tactile crayons would aid in teaching and fill a needs gap. The participants were able to discriminate the six crayons with a mean accuracy (standard error) of 77% (4%), and of those six, they could identify the four most easily discriminable with 86% (3%) accuracy. Discussion: Many families and teachers showed interest in the potential of tactile crayons as a learning tool. Four of the six tactile crayons were both highly discriminable and identifiable by adults who are visually impaired. This finding shows promise for discriminability and identifiability of these crayons by children who are visually impaired and their potential as a learning tool in both formal and informal learning environments. Implications for practitioners: The use of the developed tactile crayons has the potential to aid childhood development and student learning. In addition, the use of the crayons by teachers could help reduce the time needed to produce tactile diagrams.